(untitled) (Scientia Agropecuaria, 2021)
The cadmium absorption by cacao plant and increased in beans accumulation, represents a problem for the exports of cacao beans and chocolate industry. In this study, native strains of Trichoderma spp. were evaluated for their capacity of tolerate and removal to Cd, collected from rhizospheric soil of cacao trees. In order to evaluate such capacities under in vitro conditions, 10 native strains of Trichoderma spp. were inoculated in potato dextrose agar (PDA) culture medium contaminated with three concentrations of Cd (25 ppm, 100 ppm and 250 ppm) and in potato dextrose (PD) culture medium contaminated with 5 ppm Cd. With data of growth rhythm (RC) of the fungus colony in Cd presence and percentage of Cd removal (RCd), the analysis of variance was performed, and the means were compared with Scott-knott test (p = 0.05). The results showed that, Trichoderma spp. were sensitive to Cd presence and capable of Cd removing. Among the strains with high significant removal Cd capacity (p < 0.05) were T. brevicompactum M43D (83.1%), T. harzianum M1P (67.0%) and T. spirale M55SM (65.8%). While the most tolerant strains were T. harzianum M1P and T. koningiopsis M3B, in comparison to the control treatment without Cd. Therefore, T. brevicompactum M43D and T. spirale M55SM unite to the list of Trichoderma species as potential new Cd bioremediation agents that can be explored.